Internet Cognitive Behavioral Therapy With or Without Face-to-Face Psychotherapy: A 12-Weeks Clinical Trial of Patients With Depression - Rauen, Katrin; Vetter, Stefan; Eisele, Amanda; Biskup, Ewelina; Delsignore, Aba; Rufer, Michael; Weidt, Steffi (Frontiers in Digital Health, 2020)
Depressive disorders are a curable, global health problem. However, most patients remain untreated and more and more patients use internet-based interventions, but it is unclear whether it is beneficial for ongoing face-to-face psychotherapy. Thus, we compared the outcome of internet cognitive behavioral therapy (ICBT) with (ICBT+) or without (ICBT) additional face-to-face outpatient psychotherapy in adult patients with depressive disorder. For this longitudinal interventional clinical trial (NCT02112266), 168 out of 252 online recruited adults with depressive symptoms received ICBT+ (N=96) or ICBT (N=72). Demographics (sex, age, age at first depressive episode, years of education, duration of depressive symptoms) were assessed and compared between groups. All patients underwent ICBT for 12 weeks. Quality of life (QoL) and severity of depressive symptoms were assessed within each group at three time-points (baseline (T0), post-interventional at 12 weeks (T1), and for follow-up at six months (T2)) using the World Health Organization Quality of Life questionnaire (WHOQOL-BREF) global score as primary and the Beck Depression Inventory (BDI-II) as secondary outcome variables, respectively. Differences were assessed between groups using t-test and over time using ANOVA repeated measures. Data of ITT analysis are given as mean±SD. Group differences were assumed at p<0.05. Partial eta squared (η2) is given as effect size. Demographic data, QoL and depressive symptoms did not differ between groups (ICBT+/ICBT) at baseline. Patients of both groups suffered from moderate to severe depressive disorders and gained improved QoL scores (WHOQOL-BREF-global: p<0.001, η2=0.16) and had decreased depressive symptoms (BDI-II: p<0.001, η2=0.2) after 12 weeks of ICBT compared to baseline. Patients without additional face-to-face outpatient psychotherapy lost QoL—albeit not significant—and had increased depressive symptoms (BDI: p=0.02, η2=0.04) at six months follow-up. Thus, ICBT is suitable for psychiatric treatment though additional face-to-face outpatient psychotherapy stabilize long-term outcome.